Effect of pH and Inorganic Reagents on the Immobilization of Cadmium in Some Malaysian Cocoa-growing Soils - Low, K. S.; Lee, C. K. (Universiti Putra Malaysia Press, 1994)
The effects of pH and various inorganic reagents on the immobility of cadmium in three Malaysian cocoa-growing soils (Rengam, Bernam and Malacca) were investigated. Results show that Ca(OH)2 was most efficient in immobilizing cadmium. Carbonates and phosphates were also effective, though to a lesser extent.